PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KOMPETENSI DAN LEARNING ORGANIZATION APARATUR SIPIL NEGARA BALAI BESAR PENGAWAS OBAT DAN MAKANAN DI PEKANBARU - Martarina, Martarina; B. Isyandi, B. Isyandi (Jurnal Tepak Manajemen Bisnis, 2018)
The influence of organization culture and motivation on the competence andlearning organization of civil servants atthe House of Food and Medicine Monitoring inPekanbaru (BBPOM di Pekanbaru). This research is aimed at finding out andanalyzing the influence of organization culture and motivation on the competence andlearning organization of civil servant at the House of Food and Medicine Monitoring inPekanbaru (BBPOM di Pekanbaru).The population is all civil servant at the House ofFood and Medicine Monitoring in Pekanbaru (BBPOM di Pekanbaru) with totalnumber 96 people. The sampling technique used by the research is by taking allpopulation as the sample with census and satiation method. The analysis applied in thisresearch is two phases of double linear regression.The result of the research shows that the loose variable organization culture andmotivation collectively have positive and significant influence on civil servant at theHouse of Food and Medicine Monitoring in Pekanbaru (BBPOM di Pekanbaru).Partial assessment shows that the variable of organization culture and motivation havepositive and significant influence the competence, while fixed variable competence haspositive and insignificant influence on learning organization of civil servant at theHouse of Food and Medicine Monitoring in Pekanbaru (BBPOM di Pekanbaru).Thefactor of motivation is the most dominant factor which influence the competence of civilservants at the House of Food and Medicine Monitoring in Pekanbaru (BBPOM diPekanbaru).